Bilayer Biomaterials Cell Scaffold for Articular Cartilage Regeneration - กิตติยา ทุ่นศิริ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The full-thickness articular cartilage defect is the abnormal grade of articular cartilage injury. The injury in adolescents and young adult athletes cause long-term problems. To resume sport activity, the gold standard treatment, mosaicplasty or osteochondral autograft transfer, is recommended. This research aims to propose a combination technique of mosaicplasty and tissue engineering to eliminate the limitations of osteochondral regeneration and the complications of the treatment using biomedical engineering strategy. The bilayer biomaterials scaffold and its fabrication process are the major concern to increase treatment abilities and decrease the limitations such as time, cost and complication during the treatment using the low-cost local materials and fabrication technique. The 3D printing fused filament fabrication type was selected to fabricate the tissue-engineering scaffold due to its performance and cost effectiveness. The printing filament is required for FDM 3D printers. The biomaterials filament was considered to provide the proper abilities for articular cartilage regeneration. The biocompatible polymers: polylactic acid (PLA) and polycaprolactone (PCL) were selected to be the main structure for the filaments. The bioactive materials: hydroxyapatite (HA) and silk fibroin (SF) were locally extracted. HA was added to PLA and PCL to create PLA/PCL/15HA filament for 3D printing bone layer of the scaffold. PLA/PCL filament was 3D printed to be the cartilage layer of the scaffold. A solution of Chitosan (CS) and SF were prepared before combining with PLA/PCL printed layer using the lyophilization technique (PLA/PCL+CS/SF). The characterizations, mechanical tests, and biological tests were performed along with the fabrication processes from biomaterials extraction, biomaterials filaments extrusion, 3D printing specimens, 3D printing scaffold, and complete bilayer biomaterials cell scaffold, respectively. The results presented good morphology, non-cytotoxicity, and printing abilities of the extruded filaments. The bilayer biomaterials cell scaffold provided good environments for cell proliferation. The bioactive materials played the role in increasing cell proliferation. The presence of HA in the PLA/PCL structure increased bone cell proliferation while CS/SF increased cartilage-like cell proliferation. The mechanical properties obtained from specimen’s mechanical tests were used to predict the mechanical ability of the scaffold 3D design via a finite element analysis program. The 6 mm diameter of the cylindrical scaffold 3D design can carry a compression load up to 968 N or 96.8 kg. The whole tests confirmed the abilities of the bilayer biomaterials scaffold and its fabrication process to be used for articular cartilage and bone regeneration in full-thickness articular cartilage defect treatment.